EDUKASI PENYAKIT TUBERCULOSIS (TB) UNTUK MENINGKATKAN PENGETAHUAN WARGA DESA BARANG KECAMATAN LILIRIAJA KABUPATEN SOPPENG - Tilka Muftiah; Besse Dahlia (Jurnal Pengabdian Masyarakat Gerakan Aksi Sehat (GESIT), 2021)
Tuberculosis (TB) is still a major global health problem and ranks second as a disease causing death from all infectious diseases around the world. With this counseling activities aims to give understanding to the community about the disease Tuberculosis (TB). The method of implementation of counseling activities is that the community will be given first Test and then do an education about the disease Tuberculosis (TB), and after that was given a post test to see the change of public knowledge. The level of community knowledge before education is knowledge of 73.3% and approximately 26.7%. After education, there is an increase in knowledge is 100%.